HOW TO WRITE A RESEARCH ARTICLE: A STRUCTURED APPROACH - Dumka, Pankaj; Chauhan, Rishika; Mishra, Dhananjay R. (Sanata Dharma University, Yogyakarta, 2025)
Writing a high-quality research article requires a structured and systematic approach to ensure the clarity, coherence, and scholarly impact. This paper provides a comprehensive guide for researchers aiming to publish in academic journals. It outlines the essential components such as topic selection, literature review, methodology formulation, results presentation, discussion, and conclusion writing. The methodology section emphasizes the significance of transparency and reproducibility by offering a sample case study to illustrate each step. The paper draws from established academic writing principles and integrates practical strategies for enhancing manuscript quality. Through a step-by-step framework, the study helps the beginner and experienced researchers to improve their writing efficiency and publication success. The article also highlights the common pitfalls and provides the tips for formatting, referencing, and submission processes. Overall, this structured guide aims to bridge the gap between research execution and effective communication, supporting authors in producing impactful scholarly articles that contribute meaningfully to their respective fields.